PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN DANA OTONOMI KHUSUS TERHADAP BELANJA MODAL DI PAPUA BARAT TAHUN 2014-2018 - Theresia P. Wanma; Yundy Hafizrianda; Syaikhul Falah (Universitas Cenderawasih, 2020)
The purpose of this study was to examine and analyze the influence of PAD, DAU, DAK and DOK on Capital Expenditures in West Papua Province in 2014-2018. This study uses secondary data, namely the budget originating from PAD, DAU, DAK and DOK which are allocated for Capital Expenditures in 12 Regencies and 1 City in West Papua Province. The analytical tool used is Multiple Linear Regression with IBM SPSS 21 application.The results of the study show that local revenue, general allocation funds and special allocation funds have no effect on capital expenditure, while the special autonomy fund has a positive and significant effect on capital expenditure. Furthermore, simultaneously PAD, DAU, DAK and DOK have no significant effect on Capital Expenditures